Evaluating postoperative recovery in uniportal versus needlescopic video-assisted thoracoscopic surgery for primary spontaneous pneumothorax: a comparable study - Chuang, Jen-Hao; Hsu, Hsao-Hsun; Lin, Mong-Wei; Huang, Pei-Ming; Kuo, Shuenn-Wen; Chen, Ke-Cheng; Chen, Jin-Shing (Frontiers in Surgery, 2024)
Objectives: Primary spontaneous pneumothorax (PSP) is a common disease in young and thin male. Operation has been regarded as definitive treatment for it. However, the operative methods for those patients are under dispute. This study aims to directly compare the outcomes of uniportal VATS versus needlescopic VATS in the treatment of PSP, focusing on postoperative pain and safety outcomes. Methods: From July 2013 to December 2017, the patients who underwent video-assisted thoracic surgery for pneumothorax in National Taiwan University Hospital were retrospectively collected. The preoperative condition, surgical results, and postoperative outcomes was analyzed. Results: There were 60 patients undergoing needlescopic VATS and 91 undergoing uniportal VATS during the study period. There was no significant difference between the patients who underwent needlescopic VATS and those who underwent uniportal VATS in their demographic and clinical characteristics. The post-operative pain score was significantly lower in the uniportal VATS group compared to the needlescopic VATS group at day 1 (2.65 ± 1.59 vs. 1.74 ± 1.35, p = 0.001). Conclusion: Uniportal VATS offers an effective, safe alternative for PSP treatment, with benefits including reduced post-operative pain. Our findings support the use of uniportal VATS, supplemented by a wound protector, as a viable option for PSP patients.